PENGEMBANGAN METODE PEMBELAJARAN PAI BERBASIS KECERDASAN MAJEMUK - Asnah, Asnah, (IAIN Padangsidimpuan, 2017)
Learning Islamic education (PAI) is not only based on religious knowledge oriented, but also emphasized to the aspects of attitudes, values and skills/practice of religion. However, in practice in the classroom, teachers less developed all these aspects, meanwhile the students as subjects who have learning process experienced has a variety of intelligences that can be developed. In PAI learning, multiple intelligences is a grouping of capabilities in someone in order to function more optimally. For that is expected to each PAI teachers to develop teaching methods by taking various strategic measures for the purpose of learning can be achieved optimally